Risk factors, quality of life, and oral implications of osteoporosis in postmenopausal women - Ravleen Nagi; Yashoda Devi Bhoomareddy Kantraj; Rakesh Nagaraju; Sujatha S Reddy (Wolters Kluwer Medknow Publications, 2016)
Osteoporosis is a systemic skeletal disease characterized by low bone mass and microarchitectural deterioration of bone tissue, with a consequent increase in bone fragility and susceptibility to fracture. Low bone mineral density (BMD), age, and low body mass index have been found to be major risk factors for osteoporosis. Postmenopausal women with low BMD had thinner mandibular cortex at the mental foramen region and more alveolar bone loss when compared to normal participants, and they are more susceptible to femoral neck fractures. Osteoporotic patients show various oral manifestations; more tooth loss, periodontitis, and decrease in alveolar crestal height. This review will focus on the relationship between osteoporosis and oral conditions such as periodontitis, tooth loss, and oral bone loss.